2023
DOI: 10.1371/journal.ppat.1011507
|View full text |Cite
|
Sign up to set email alerts
|

Aminopeptidase MNP-1 triggers intestine protease production by activating daf-16 nuclear location to degrade pore-forming toxins in Caenorhabditis elegans

Abstract: Pore-forming toxins (PFTs) are effective tools for pathogens infection. By disrupting epithelial barriers and killing immune cells, PFTs promotes the colonization and reproduction of pathogenic microorganisms in their host. In turn, the host triggers defense responses, such as endocytosis, exocytosis, or autophagy. Bacillus thuringiensis (Bt) bacteria produce PFT, known as crystal proteins (Cry) which damage the intestinal cells of insects or nematodes, eventually killing them. In insects, aminopeptidase N (AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 67 publications
(112 reference statements)
0
0
0
Order By: Relevance
“…Trichoderma harzianum has been reported to be able to control root-knot nematode disease, and a protease produced by it plays an important role in the control of root-knot nematodes (Meloidogyne incongnita) [37]. Bacillus thuringiensis and Bacillus cereus can also produce one or several proteases or other secondary metabolites, which severely damage the eggshell [38][39][40]. Fallahzadeh et al [41] obtained a strain of Bacillus wiedmannii and reported that the control of root-knot nematodes depends mainly on producing highly active chitinase, which destroys the eggs and eggshells of J2.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Trichoderma harzianum has been reported to be able to control root-knot nematode disease, and a protease produced by it plays an important role in the control of root-knot nematodes (Meloidogyne incongnita) [37]. Bacillus thuringiensis and Bacillus cereus can also produce one or several proteases or other secondary metabolites, which severely damage the eggshell [38][39][40]. Fallahzadeh et al [41] obtained a strain of Bacillus wiedmannii and reported that the control of root-knot nematodes depends mainly on producing highly active chitinase, which destroys the eggs and eggshells of J2.…”
Section: Discussionmentioning
confidence: 99%
“…The action mechanism of Bacillus in controlling plant root-knot nematodes is (1) to compete for nutrients and space; (2) to alter the action mode of root exudates and nematodes; (3) to produce toxic substances that are fatal for root-knot nematodes; and (4) to generate secondary metabolites that inhibit egg hatching and larval development [44]. Currently, Bacillus has been isolated and screened for the control of root-knot nematodes, including Bacillus thuringiensis [38], Bacillus amyloliquefaciens [45], Bacillus subtilis [46], Bacillus simplex [47], Bacillus firmus [48], Bacillus pumilus [49], Bacillus mycoides [50], and Bacillus megaterium and Bacillus cereus [9]. Peribacillus frigoritolerans is a multifunctional strain with the characteristics of preventing and controlling soil-borne diseases, promoting plant growth, and tolerating low temperature and saline-alkali environments [51].…”
Section: Discussionmentioning
confidence: 99%